GANGGUAN ASTENIK ORGANIK PADA PASIEN GRAVES’ DISEASE DAN STROKE NON-HEMORAGIK: LAPORAN KASUS - Permatasari, Intan; Setyawati Kurniawan, Lely; Aju Kusuma Wardani, Ida; Ana Mahardika, I Komang (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
Graves’ disease is an autoimmune condition that may lead to various neuropsychiatric manifestations, including mood disorders, anxiety, chronic fatigue, and cognitive dysfunction. One underrecognized presentation is organic asthenic disorder (F06.6), which may result from combined endocrine and neurological impairments. To report and analyze a case of organic asthenic disorder in a young female with active Graves’ disease and a history of non-hemorrhagic stroke, emphasizing the importance of identifying secondary psychiatric syndromes in chronic medical conditions. The patient presented with severe fatigue, emotional dysphoria, mixed insomnia, and unexplained physical pain and paresthesia. Laboratory findings confirmed hyperthyroidism, while neurological examination showed right-sided weakness due to prior stroke. The diagnosis of Organic Asthenic Disorder was made based on the clinical and temporal relationship with thyroid and neurological dysfunction. Management involved antithyroid medication, propranolol, low-dose haloperidol, and supportive therapy with family psychoeducation. Organic asthenic disorder represents a significant clinical concern in liaison psychiatry, particularly among patients with overlapping endocrine and neurological disorders. Accurate diagnosis and multidisciplinary management are essential to avoid misdiagnosis and improve psychosocial outcomes. ABSTRAK Graves’ disease merupakan kondisi autoimun yang dapat menimbulkan berbagai manifestasi neuropsikiatri, termasuk gangguan mood, kecemasan, kelelahan kronis, dan disfungsi kognitif. Salah satu bentuk presentasi yang jarang dikenali adalah gangguan astenik organik (F06.6), yang dapat terjadi akibat kombinasi disfungsi endokrin dan neurologis. Melaporkan dan menganalisis satu kasus gangguan astenik organik pada seorang perempuan muda dengan Graves’ disease aktif dan riwayat stroke non-hemoragik, serta menekankan pentingnya identifikasi sindrom psikiatri sekunder dalam kondisi medis kronis. Pasien datang dengan keluhan berupa kelelahan berat, disforia emosional, insomnia campuran, serta nyeri fisik dan parestesia yang tidak dapat dijelaskan secara medis. Pemeriksaan laboratorium mengonfirmasi adanya hipertiroidisme, sementara pemeriksaan neurologis menunjukkan kelemahan sisi kanan akibat riwayat stroke. Diagnosis Gangguan Astenik Organik ditegakkan berdasarkan hubungan temporal dan klinis dengan disfungsi tiroid dan neurologis. Terapi meliputi pemberian obat antitiroid, propranolol, haloperidol dosis rendah, serta terapi suportif dan psikoedukasi keluarga. Gangguan astenik organik merupakan masalah klinis penting dalam psikiatri liaison, terutama pada pasien dengan komorbiditas endokrin dan neurologis. Diagnosis yang tepat dan penanganan multidisiplin diperlukan untuk mencegah salah diagnosis dan meningkatkan luaran psikososial pasien.